METHODOLOGY OF KNOWLEDGE RESOURCES AUDIT FOR FORMATION OF PHARMACY ORGANIZATION ASSORTMENT - I. M. Razdorskaya; K. V. Danilova (Фармация и фармакология (Пятигорск), 2015)
The timeliness of this subject is conditioned by the increase of a role of knowledge in pharmacy organizations (PO) management, significance increase of non-material assets in a competition on the pharmaceutical market. The development and substantiation of methodology of knowledge resources audit significance on the example of drug assortment formation for allergic rhinitis treatment. We have used sociological, statistic, expert methods of a study. Close attention was paid to the method of target management, construction of target tree. The construction of the target tree of the knowledge resources audit was based on the main target establishment, targets of the first level, and eight subtargets. We have offered new special positions of assortment formation. “Formation of consumers’ loyalty” is the target of the first level, subtargets “Analysis of clients preferences”, “Transformation of clients preferences”, “Positioning of consumers by the compliance degree”. We have determined the relevance significance by the main target achievement – rational assortment formation. We have shown that the achievement of the first level target “Formation of consumers’  loyalty” conduce the achievement of the main target by 40%. The analysis of the current assortment and a process of assortment upgrading guarantee the achievement of the target by 30% each. The methodology is prospective for knowledge resources audit by the principal business processes of pharmacy organizations.